PUBLIC RELATIONS MANAGEMENT STRATEGY TO INCREASE COMMUNITY PARTICIPATION IN EDUCATIONAL INSTITUTIONS - Fathan Zaini (Universitas Nurul Jadid, 2024)
This research focuses on evaluating the effectiveness of Public Relations management strategies implemented in Islamic-based junior high schools in increasing community participation. The main aim of this research is to examine how various communication techniques, including oral, written, and concrete action communication (Uswa Hasana), as well as the use of social media, can influence the engagement of people from heterogeneous backgrounds. The research method used is descriptive qualitative with a case study approach. Data was collected through in-depth interviews, participant observation, and document analysis. The data analysis technique used is thematic analysis, which allows the identification of key themes relevant to the research objectives. The research results show that the combination of communication techniques applied was successful in increasing community participation. Oral communication through meetings and discussions, written communication through pamphlets and social media, as well as concrete actions through social and religious activities, all play an important role in reaching and involving the community. The use of social media has proven effective in disseminating information quickly and efficiently. In addition, a strong leadership role in coordinating and motivating the PR team is very influential in the success of the communications program. The implications of this research indicate that PR management strategies that integrate various effective communication and leadership techniques can significantly increase community participation in school activities.